Over a million students use our free study notes to help them with their homework
Assume that Tom's age now is x and that his dad's is 3x. Therefore, in 15 years Tom will be x+15 years old and his dad will be 3x+15 years old. Since the sum of their ages will be equal to 102, we can f...
It seems like f(x+2) should translate the graph y=f(x) 2 to the right, it is +2 inside the bracket after all? However, if we think of the translation as actually subbing in x+2 into the equation y=f(x), i...
4x/(x2-9)-2/(x+3) = 4x/((x+3)(x-3))-2/(x+3) = 4x/((x+3)(x-3))-2(x-3)/((x+3)(x-3)) = (4x-2(x-3))/((x+3)(x-3)) = (2x+6)/((x+3)(x-3) = (2(x+3))/((x+3)(x-3)) = 2/(x-3)
For x = 2, y = 16. Calculate the gradient of the curve at y = 2, dy/dx = 6x^2, dy/dx = 24. This is also the gradient of the tangent to the curve at x = 2. It is a rule that the products of the gradients o...
This question challenges a students skills with integration and trigonometry a very common question on Core 4 papers that can leave students struggling. First we use our knowledge that cosecy=1/siny and m...
←
696
697
698
699
700
→
Internet Safety
Payment Security
Cyber
Essentials